Research on Economics Growth and Development as Doctor of Letters in Economics - Iqbal Shaukat (Formad English Foundation NTB Jakarta, 2026)
Economic development is a continuous process.it is not possible in one years,it takes the many years,the impact of economic development is very long.Economic development is the right example of revolution.Economic development is the very integral part of country human life.Some countries are symbol of Economic development.All the nation should fellow the path way of development..Many countries are the examples for other world.Deregulation,cottage industry,Micro finance, Motivation economic and management policies.Such economy got the destination of Economic development with steadily and smoothly.for example in china and Japan have the economic growth target of two percentage,through this way they achieved the economic growth and devlopment.